Pemberdayaan Masyarakat Desa Wonorejo, Kec. Pagerwojo, Kabupaten Tulung Agung Menuju Masyarakat Desa Ekologi - Nugraheni Hadiyanti; Devina Cinantya Anindita; Adam Mahardika (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2022)
Integrated and sustainable rural management according to the function of natural resources, carried out based on local values and wisdom. It aims to maintain the sustainability and balance of nature for the sustainability of life from generation to generation. The realization of an ecological village is not without technology and mechanization, but it is adjusted to local needs and conditions. The community service team initiated the community empowerment program in Wonorejo Village, Pagerwojo District, Tulungagung Regency, toward an ecological village from the Faculty of Agriculture, Kadiri University. This activity is a form of the team's concern for the conditions in Wonorejo Village, which is experiencing a decline in forest function, soil productivity, and water sources. The activities carried out include improving soil structure with organic materials, producing vegetable pesticides, and conserving soil and water. Farmers who participated in the extension and training welcomed this activity and entirely understood the concept of an ecological village globally. This activity is beneficial for increasing agricultural land productivity and the surrounding environment. The positive impact of this activity is the community's interest in applying organic materials in their agrarian business to maintain the sustainability and balance of nature.Â Pengelolaan pedesaan yang terpadu dan berkelanjutan sesuai fungsi sumberdaya alam diselenggarakan berdasarkan nilai-nilai dan kearifan lokal setempat. Hal ini dimaksudkan untuk menjaga kelestarian dan keseimbangan alam demi keberlangsungan kehidupan dari generasi ke generasi. Terwujudnya desa ekologi bukan tanpa teknologi dan mekanisasi akan tetapi pemakaiannya disesuaikan kebutuhan dan kondisi setempat. Program pemberdayaan masyarakat Desa Wonorejo Kecamatan Pagerwojo Kabupaten Tulungagung menuju desa ekologi diinisiasi tim pengabdian masyarakat Fakultas Pertanian Universitas Kadiri. Kegiatan ini sebagai bentuk kepedulian tim terhadap kondisi di Desa Wonorejo yang mengalami penurunan fungsi hutan, produktivitas tanah, dan sumber air. Kegiatan yang dilaksanakan adalah perbaikan struktur tanah dengan bahanbahan organik, pembuatan pestisida nabati, konservasi tanah dan air. Petani peserta penyuluhan dan pelatihan menyambut dengan baik kegiatan ini dan cukup memahami konsep desa ekologi secara global. Kegiatan ini bermanfaat untuk peningkatakan produktivitas lahan pertanian dan lingkungan sekitarnya. Dampak positif dari kegiatan ini adalah ketertarikan masyarakat dalam mengaplikasikan bahan-bahan organik dalam usaha pertanian mereka demi menjaga kelestarian dan keseimbangan alam.